Winning When It Really Counts: Quick, Easy Strategies For Success In Any Speaking Situation - Arch Lustberg
Gives advice on effectively using one's face, gestures, and voice for public speaking, tells how to prepare a speech, and discusses courtroom testimony, job interviews, meetings, negotiation, sales, and teaching.